Improvement in Thermal Efficiency of a CI Engine Using a Waste Heat Recovery Technique - Sharma, Aashish; Chauhan, Ajay; Nautiyal, Himanshu; Varun; Sharma, Pushpendra Kumar (Asian Journal of Engineering and Applied Technology, 2015)
A big portion of the heat supplied to an internal combustion (IC) engine is not converted into work and wasted through the exhaust gases in surroundings. If this heat is recovered or used by some means then improvement can be obtained in engine’s overall efficiency. In the present work, an experimental work is carried out to study the effect of waste heat recovery of exhaust gas in a Compression Ignition (CI) engine. The results show that considerable reduction in engine fuel consumption can be obtained with the help of exhaust heat recovery through a heat exchanger. A significant amount of heat of exhaust gases can be recovered by vaporization of fuel using a heat exchanger.